Práticas de letramentos em língua portuguesa como língua adicional para surdos em uma escola pública - Furlaneto, Lucimeire da Silva (2020)
In this doctoral thesis, which was evolved in a public school in a capital city in the Midwest region of the country, it is my objective to investigate how teaching practices of literacy in Portuguese as an additional language to deaf students in the 9th grade of elementary school occur. I used the contributions of theories on the education of the deaf (SKLIAR, 2016; 2013; 2002), (FERNANDES, 2006a; 2006b; 2003), (PEREIRA, 2014; 2011), (GÓES, 2015; 2013; 2012), (RANGEL; STUMPF, 2015), (LODI; HARRISON; CAMPOS, 2013), and others. The theoretical support affiliate to the studies on literacy practices, which conceives language, in this context, as a social practice of reading and writing, under the eyes of (STREET, 2010; 1995; 1984), (SOARES, 2012; 2010 ; 1998), (KLEIMAN, 1999; 1998; 1995) (PAN, 2006). In addition, it focuses on the key concepts of the autonomous and ideological literacy models, according to (STREET, 2010; 1995), with an emphasis on the teaching of Portuguese language, articulated to the conceptions of language in the perspectives of Bakhtin/Volochinov (2012), (GERALDI, 1996; 1993; 1984), (FUZZA; MENEGASSI, 2011) and others. The thesis is organized in three chapters, in addition to the introduction and final considerations. This organization includes research questions, which are answered and general objectives and specific ones, which are achieved. The methodological approach is qualitative (BOGDAN; BIKLEN, 1994), of a participatory nature, according to Gil (2009). For the data generation, three moments were observed. The first consisted of observing ten class-hours taught by the research subject, the second, observing literacy practices in the school space, and the third, as a researcher-participant with the teacher in six class-hours. Analyzing the three moments, I was able to answer the three research questions: (1) How does Portuguese language teaching as an additional language to deaf students in the 9th grade of elementary school, in a public school in a capital in the Midwest region of the country? (2) What literacy practices are verified in the school space? (3) What sense(s) does the teacher attribute to the process of teaching reading and writing to deaf students? The results showed that the teaching of the Portuguese language took place from the same perspective as the traditional teaching of reading and writing in other schools, other than the one not studied. Already in the classes in which I participated acting in cooperation with the teacher, when we took, teacher and I, the teaching of LP as an additional language to deaf students as a social practice of language, the result pointed to a much more significant learning, especially when there was, in this process , a conception of language as interaction and a view of the student as the central subject of this action, from the perspective of a different subject, given their identity peculiarities, and not disabled. As for literacy practices in the school corridor, these differ little from the practices taught in schools considered “regular”. About the senses produced, these emerged much more during the classes in which the teacher agreed to change the content, as well as the language perspective adopted until then; because I noticed a greater involvement of the students with the themes worked on. Finally, it is important that the topic of this thesis does not end here and that it can contribute to future research, discussions and reflections, given my observations, how much more and more studies on continuing education for teachers teaching students are needed and urgent deaf, due to their initial formation with such fragility, not to mention with such precariousness.